Pengaruh Penerapan Interprofessional Education Terhadap Pengetahuan, Sikap Dan Perilaku Remaja Tentang Menstrual Hygiene Management - Nabila Amelia Hanisyahputri; Sri Ramadany; Muhammad Tamar; Sabrina Dwi Prihartini; Anita Dwi Agustina Sari (Oksitosin : Jurnal Ilmiah Kebidanan, 2020)
Women and girls struggle to manage menstruation caused by the lack of information obtained. Lack of access to information tends to be experienced by young women who live in pesantren. One effort to realize good collaboration is through the educational process, for example IPE (Interprofessional education). IPE is an innovation that is being developed in the world of the health profession which aims to improve health services through collaboration between health workers. The purpose of this study was to determine the effect of the application of IPE conducted by health students on the knowledge, attitudes and behavior of adolescents about menstrual hygiene management. This was an observational quantitative study with pre-post test control group design. A sample of 40 young women in the intervention group and 40 control groups. The results showed a significant effect on the intervention group receiving education by the IPE method from health students. The implementation of IPE in the form of education to young women can influence the improvement of knowledge, attitudes and behavior of adolescents towards menstrual hygiene management. Keywords: Interprofessional Education, Management of menstrual hygiene, young women, boarding schools. ABSTRAK Wanita dan anak perempuan kesulitan dalam mengelola menstruasi diakibatkan oleh kurangnya informasi yang diperoleh. Kurangnya akses informasi cenderung dialami oleh remaja putri yang tinggal di pesantren. Salah satu upaya untuk mewujudkan kolaborasi yang baik yaitu melalui proses pendidikan, misalnya IPE (Interprofessional education). IPE merupakan suatu inovasi yang sedang dikembangkan dalam dunia profesi kesehatan yang bertujuan untuk meningkatkan pelayanan kesehatan melalui kolaborasi antar tenaga kesehatan. Tujuan penelitian adalah untuk mengetahui pengaruh penerapan IPE yang dilakukan oleh mahasiswa kesehatan terhadap pengetahuan, sikap dan perilaku remaja tentang manajemen kebersihan menstruasi. Ini merupakan penelitian kuantitatif observasional dengan pre-post test control group design. Sampel sebanyak 40 remaja putri kelompok intervensi dan 40 kelompok kontrol. Hasil penelitian menunjukkan terdapat pengaruh yang signifikan pada kelompok intervensi yang menerima edukasi dengan metode IPE dari mahasiswa kesehatan. Pengimplementasian IPE dalam bentuk edukasi kepada remaja putri dapat mempengaruhi peningkatan pengetahuan, sikap dan perilaku remaja terhadap manajemen kebersihan menstruasi. Keywords: Interprofessional Education, Manajemen kebersihan menstruasi, remaja putri, pesantren.